Teknik Brain Gym untuk Meningkatkan Konsentrasi Belajar Ditinjau dari Tingkat Intelligence Quotient Peserta Didik - Yesi Kartini; Asrowi Asrowi; Edy Legowo (Jurnal Psikoedukasi dan Konseling)
Abstract: This study aims to examine the use of brain gym techniques to increase learning concentration in terms of the IQ level of students. The research method used is a literature study. Sources of data using reference books, articles, and research journals. The data analysis technique was a content analysis that was then checked for contents between libraries and expert input to avoid misinterpretation due to the author's limitations. The study's results found that: 1) Learning concentration is the ability to focus on the learning activities being carried out or faced by ignoring external disturbances. 2) IQ is the ability of a person that is innate from birth by involving the process of thinking quickly, precisely, and rationally in acting. 3) Brain gym is a series of fun, simple motion exercises to facilitate learning activities by balancing the left and right brain. The conclusion of this study is that brain gym techniques are effective for increasing learning concentration in terms of the IQ level of students.